Tools of thinking. understanding the world through experience and reason - Hall, James, 1933-; Teaching Company (Chantilly, VA : Teaching Co., 2005)
Twenty four separate lectures about the human thought process.
"The purpose of this course is to trace out in a semi-historical way how modern rational empiricism has arrived at its tool kit for thinking (a tool kit particularly well modeled by modern natural science but also employed in a wide variety of other, everyday, enterprises)"--P. 1.
pt. 1: Lecture 1: What are "Tools of Thinking?" -- Lecture 2: Which tools of thinking are basic? -- Lecture 3: Platonic intuition, memory, and reason -- Lecture 4: Intuition, memory, and reason--problems -- Lecture 5: Sense experience--a more modern take -- Lecture 6: Observation and immediate inferences -- Lecture 7: Further immediate inferences -- Lecture 8: Categorical syllogisms -- Lecture 9: Ancient logic in modern dress -- Lecture 10: Systematic doubt and rational certainty -- Lecture 11: The limits of sense experience -- Lecture 12: Inferences demand relevant evidence. pt. 2: Lecture 13. Proper inferences avoid equivocation -- Lecture 14. Induction is slippery but unavoidable -- lecture 15. The scientific revolution -- Lecture 16. hypotheses and experiments-- a first look -- Lecture 17. How empirical is modern empiricism? -- Lecture 18. Hypotheses and experiments--a closer look -- Lecture 19. "Normal Science" at mid-century -- Lecture 20. Modern logic--truth tables -- Lecture 21. Modern Logic--Sentential arguments -- Lecture 22. Modern logic--predicate arguments -- Lecture 23. Postmodern and new-age problems -- Lecture 24. Rational empiricism in the 21st century.
Lectures 13-24 of 24 presented by Professor James Hall, University of Richmond.
Keywords: Thought and thinking; Empiricism; Audiobooks